Estudo experimental da fotobiomodulação em modelo de coabitação entre camundongos com tendinite e camundongos com tumor de bexiga induzido - Makabe, Marcia Aparecida (2019)
Cohabitation is related to the act of living with people with certain diseases and there may be psychological, behavioral and immunological changes. Tendinopathies are changes in the tendon, usually difficult to treat, where photobiomodulation therapy has been shown to have good effects. The works relating changes in the cohabitation model and its reflex in tendon repair in the acute phase of inflammation are rare. In the same sense, a study of the effect of cranial photobiomodulation on the modulation of the peripheral inflammatory process as in tendinopathies is non-existent. The objective of this work was to evaluate the effect of photobiomodulation on the inflammatory process of the tendon in mice cohabited with animals with induced bladder tumor. Material and Methods: Forty female C57BL / 6 mice were divided into 4 groups: (Group 1): Animals with induced tendonitis, untreated and cohabited with healthy mice; (Group 2): Animals with induced tendinitis, treated with LED cranial therapy and cohabited with healthy mice; (Group 3): Animals with induced tendonitis, untreated and cohabited with mice with bladder tumor; (Group 4): Animals with induced tendinitis, treated with LED cranial therapy and cohabited with mice with tumor. Tendonitis was performed after 2 weeks of cohabitation. The 20 healthy animals were induced to tendinitis with collagenase injection (100ml / kg) in the region of the calcaneus tendon. The irradiation parameters were: (LED 810nm; 3J; 160mW; 30s). After 12 h of tendinitis induction, the animals of the 4 groups were euthanized with hyperdose of Xilasina and ketamine. The tendons were removed and stored for molecular and histological analysis. Results: Group 3 animals reduced COX-2 expression; IL1β; IL6 and increased NK-1. Similar results were observed with the animals of group 2. The inflammatory infiltrate was also reduced in groups 2, 3 and 4. Conclusion: Animals with tendinitis in cohabitation with animals with bladder tumor present a lower inflammatory scenario than animals that cohabited with healthy mice. Cranial photobiomodulation therapy using LED was effective in reducing tendinitis inflammation in cohabitated animals with healthy mice. However, further analysis is required to determine the mechanism of action involved.